Choice without Equity: Charter School Segregation - Frankenberg, Erica; Siegel-Hawley, Genevieve; Wang, Jia (Education Policy Analysis Archives, 2011)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <mce:style><! st1\:*behavior:url(#ieooui) –> <!–[endif]–> <!–[endif]–> The political popularity of charter schools is unmistakable. This article explores the relationship between charter schools and segregation across the country, in 40 states, the District of Columbia, and several dozen metropolitan areas with large enrollments of charter school students in 2007-08. The descriptive analysis of the charter school enrollment is aimed at understanding the enrollment and characteristics of charter school students and the extent to which charter school students are segregated, including how charter school segregation compare to students in traditional public schools. This article examines these questions at different levels, aggregating school-level enrollment to explore patterns among metropolitan areas, states, and the nation using three national datasets. Our findings suggest that charters currently isolate students by race and class. This analysis of recent data finds that charter schools are more racially isolated than traditional public schools in virtually every state and large metropolitan area in the nation. In some regions, white students are over-represented in charter schools while in other charter schools, minority students have little exposure to white students. Data about the extent to which charter schools serve low-income and English learner students is incomplete, but suggest that a substantial share of charter schools may not enroll such students. As charters represent an increasing share of our public schools, they influence the level of segregation experienced by all of our nation’s school children. After two decades, the promise of charter schools to use choice to foster integration and equality in American education has not yet been realized.